The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10637-008-9115-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of the ribonucleotide reductase inhibitor 3-aminopyridine-2-carboxaldehyde-thiosemicarbazone (3-AP) in combination with high dose cytarabine in patients with advanced myeloid leukemia

Abstract: SummaryPurpose-This Phase I dose escalation study was based on the hypothesis that the addition of 3-aminopyridine-2-carboxaldehyde-thiosemicarbazone (3-AP) to cytarabine would enhance cytarabine cytotoxicity. The primary objective of the study was to establish the maximum tolerated dose of 3-AP when given in combination with a fixed dose of cytarabine.Experimental design-Twenty-five patients with relapsed or refractory myeloid leukemia were enrolled to three dose levels of 3-AP. Cytarabine was administered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 15 publications
(28 reference statements)
1
42
0
Order By: Relevance
“…Hypoxia and methemoglobinemia are major concerns for patients undergoing anticancer therapies who have compromised cardiopulmonary function (Yen et al, 2004;Knox et al, 2007;Odenike et al, 2008;Traynor et al, 2010). Recent studies demonstrated that 3-AP led to metHb generation and hypoxia in patients, limiting its usefulness (Yen et al, 2004;Gojo et al, 2007;Knox et al, 2007;Odenike et al, 2008;Traynor et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxia and methemoglobinemia are major concerns for patients undergoing anticancer therapies who have compromised cardiopulmonary function (Yen et al, 2004;Knox et al, 2007;Odenike et al, 2008;Traynor et al, 2010). Recent studies demonstrated that 3-AP led to metHb generation and hypoxia in patients, limiting its usefulness (Yen et al, 2004;Gojo et al, 2007;Knox et al, 2007;Odenike et al, 2008;Traynor et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that 3-AP led to metHb generation and hypoxia in patients, limiting its usefulness (Yen et al, 2004;Gojo et al, 2007;Knox et al, 2007;Odenike et al, 2008;Traynor et al, 2010). The mechanism responsible was not known and in consideration of the interest in the development of novel thiosemicarbazones as anticancer agents (Yu et al, 2009), it was crucial to investigate their effect on oxyHb, as this would facilitate the development of these compounds (Yu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we enter to a new era of phase 1 clinical trials investigating associations of cytotoxic agents plus molecular targeted therapies. In these new studies, the cytotoxic agents drive the toxicity profile and are the key-element that determines the dose-limiting toxicity and then maximal tolerated dose [28][29][30][31][32]. Phase I trials investigating cytotoxic drugs enroll vulnerable patients not amenable to forms of treatment with established efficacy.…”
Section: /119 (16%)mentioning
confidence: 99%
“…Research on cytotoxic properties of thiosemicarbazone-metal complexes have been centralized to platinum and palladium chelates. The object of the published papers is the ONS and NNS chelators such as benzaldehyde, 2-acetyl pyridine, phenanthrenequinone, and 2-benzoylpyridine derivatives which have no substituent on sulphur atom of thiosemicarbazone [9,10,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%